Understanding Filipino values : a management approach - Andres, Tomas D (Quezon City, 2005)
This book encourages the reader to become more sensitive to and concerned with Filipino values, enabling him to restructure and reorient these values intelligently for business management effectivity and productivity. The reader's ability to think critically on current and emerging issues and problems affecting productivity and organizational effectiveness on the basis of a fully understood Filipino value system is further developed.
Keywords: Values Filipino